Dirāsah Taḥlīlīyah lil-Ḥikam al-‘Arabīyah (Arabic Quotes) ‘alá al-Instaghrām min Manẓūr Ṭalabat Qism Ta‘līm al-Lughah al-‘Arabīyah - Wafiroh, Evi Zulfatun; Asy'ari, Hasyim; Zibrija, Fiki Roi’atuz (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This research aims to identify and analyze the productivity of the Quotes on Instagram @bahasaarabituindah and students' perception of its cognitive, emotional, and behavioral aspects. This research is a qualitative descriptive research and refers to the type of field research in Arabic Quotes on Instagram @bahasaarabituindah and students' perception of these Quotes. Data was collected in three ways: Observation, documentation, and questionnaire. The research findings are the productivity of the Instagram account @bahasaarabituindah in providing Arabic quotes for one semester in the 2022/2023 academic year about fifteen times per month. The categories of sentences are divided into ten: Affirmative, Negative, Command, Prohibition, Conditional, Interrogative, Begging, Wishing Sentence, Assertion, and Praying Sentence. Most students use Instagram frequently and visit general and humorous accounts. They know the accounts that offer arabic quotes but few of them know the account @bahasaarabituindah. Some students read arabic quotes from this account and find them interesting. Their favorite topic is living and they feel happy after reading the sayings. They may save quotes that suit their circumstances but few of them share them on social media. The design of Instagram @bahasaarabituindah influences the interest in reading sayings and can help increase students' vocabulary.